2019
DOI: 10.1002/tesq.545
|View full text |Cite
|
Sign up to set email alerts
|

“It Is More Expressive for Me”: A Translingual Approach to Meaningful Literacy Instruction Through Sijo Poetry

Abstract: Through a qualitative analysis of one-on-one poetry workshops, this article explores ways in which a Korean American adult-Author 2 (Park)-develops translingual dispositions (Lu & Horner, 2013) and linguistic awareness of Korean. Situated within the translingualism literature (e.g., Canagarajah, 2017), sijo, a type of Korean poetry, became a conduit for gaining a greater insight into how meaningful literacy (Hanauer, 2012) can be enacted. The authors conceptualize the sijo composition session as a translanguag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 47 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…Creative writing activity for poetry or books is documented in three articles (Barbour & Quinn, 2020;Kim & Park, 2020;Rowe, 2019). In the multilingual class observed by Barbour and Quinn (2020), students are encouraged to write poems using English and other languages outside school.…”
Section: Creative Writingmentioning
confidence: 99%
“…Creative writing activity for poetry or books is documented in three articles (Barbour & Quinn, 2020;Kim & Park, 2020;Rowe, 2019). In the multilingual class observed by Barbour and Quinn (2020), students are encouraged to write poems using English and other languages outside school.…”
Section: Creative Writingmentioning
confidence: 99%
“…Meaningful literacy instruction has been incorporated in classroom contexts by using the genre of poetry (e.g., Furman et al, 2007 ; Hanauer, 2012 , 2015 ; Iida, 2012 , 2016 ; Kim and Park, 2020 ). This pedagogy has extended both the breadth and depth of research from western countries (e.g., Hanauer, 2012 , 2015 ) to Asian countries, such as Japan and Korea in L2 writing contexts (e.g., Iida, 2012 , 2016 ; Kim and Kim, 2018 ; Kim and Park, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meaningful literacy instruction has been incorporated in classroom contexts by using the genre of poetry (e.g., Furman et al, 2007 ; Hanauer, 2012 , 2015 ; Iida, 2012 , 2016 ; Kim and Park, 2020 ). This pedagogy has extended both the breadth and depth of research from western countries (e.g., Hanauer, 2012 , 2015 ) to Asian countries, such as Japan and Korea in L2 writing contexts (e.g., Iida, 2012 , 2016 ; Kim and Kim, 2018 ; Kim and Park, 2020 ). For example, Hanauer (2012) investigated poetry in second/foreign language classrooms in a United States university and found that learners were more willing to express themselves in the process of learning a foreign language and could have the experience of self-exploration and self-reflection and produce meaningful content.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations